TERAPI AIR KH. JA’FAR SHODIQ DALAM MENANGANI MAHASANTRI KESURUPAN DI IDIA PRENDUAN SUMENEP MADURA - Kartini Kartini (Al-Amien Prenduan for Islamic Institute, 2020)
AbstractBeing possessed comes from the disturbance such as jinn and so on, the cause is the jinns consider the human body good so that the jinn likes to live in an empty human body and heart, or because the jinn wants to inflict interference on humans. so in this case as a healing process a lot of methods are applied by therapists, one of which is water therapy used by KH. Ja'far SHodiq and the therapies no in place who possessed. The problem raised in this research is how the process of implementing water therapy with messages of healing prayers to students possessed at IDIA Prenduan Sumenep Madura, which is described in three focus. Namely: 1. How the implementation of water therapy KH. Ja'far Shodiq in dealing with possessed mahasantri, 2. What are the prayers used as messages in KH water therapy. Ja'far Shodiq in dealing with possessed mahasantri, 3. How is the impact of water therapy KH. Ja'far Shodiq in handling possessed mahasantri. To find out more about this water therapy, the researchers used a qualitative field research approach. The method used is the method of interview, observation, and documentation. . For the validity of the data, the researcher uses the validity of the data, the researcher uses triangulation with triangulation between methods.Keyword: Teraphy, Water, Possessed